Discovery of a large Hi ring around the quiescent galaxy AGC 203001. Issue 1 (23rd October 2019) - Bait, Omkar; Kurapati, Sushma; Duc, Pierre-Alain; Cuillandre, Jean-Charles; Wadadekar, Yogesh; Kamphuis, Peter; Barway, Sudhanshu
ABSTRACT: Here we report the discovery with the Giant Metrewave Radio Telescope of an extremely large (∼115 kpc in diameter) H i ring, located around a massive quenched galaxy, AGC 203001, but off-centred with respect to it. This ring does not have any bright extended optical counterpart unlike several other known ring galaxies. Our deep g -, r-, and i -band optical imaging of the H i ring, using the MegaCam instrument on the Canada–France–Hawaii Telescope, shows however several regions with faint optical emission at a surface brightness level of ∼28 mag arcsec −2 . Such an extended H i structure is very rare with only one other case known so far – the Leo ring. Conventionally, off-centred rings have been explained by a collision with an 'intruder' galaxy leading to expanding density waves of gas and stars in the form of a ring. However, in such a scenario the impact also leads to large amounts of star formation in the ring that is not observed in the ring presented in this paper. We discuss possible scenarios for the formation of such H i -dominated rings.